Efficacy of antiparasitic macrocyclic lactone drops against passalurosis and psoroptic mange in rabbits - B. A. Diallo; S. A. Shemyakova; I. I. Tsepilova; K. E. Pozhethnyh (Российский паразитологический журнал, 2024)
The purpose of the research is to study the efficacy of a macrocyclic lactone drug using the spot-on method against passalurosis and psoroptic mange in rabbits.Materials and methods. The study was conducted at the Department of Parasitology and Veterinary-Sanitary Expertise of the MVA named after K. I. Skryabin in 2022–2023 to determine the efficacy of antiparasitic drops (active ingredients: phenylpyrazole derivative, pyrazinoisoquinoline derivative, macrocyclic lactone, insect growth regulator, manufactured by AVZ S-P, LLC) against passalurosis and psoroptic mange. The antiparasitic drops were applied by the spot-on method to rabbits of different age and sex groups in doses of 0.5 mL per animal for body weight of up to 4 kg and 1 mL per animal for body weight of 4 to 8 kg against passalurosis and psoroptic mange. Rabbit fecal samples were examined using the Fülleborn method. Skin scrapings from the inner auricle surface were studied for Psoroptes cuniculi mites as per D. A. Priselkova.Results and discussion. The antiparasitic drug was found to have 100 % efficacy against ticks Psoroptes cuniculi and nematodes Passalurus ambigus.